2018
DOI: 10.25100/socolen.v42i1.6664
|View full text |Cite
|
Sign up to set email alerts
|

Entomopathogenic nematodes in the control of cassava root mealybug Dysmicoccus sp. (Hemiptera: Pseudococcidae)

Abstract: The objective of this work was to evaluate the efficiency of entomopathogenic nematodes in the control of cassava root mealybug Dysmicoccus sp. under laboratory and greenhouse conditions. Cochineals were reared in “Cabotiá” pumpkin in climatic chambers at 27 ± 1 °C, with relative humidity (RH) of 70 ± 10%, and without photoperiod. The selection test was carried out with 15 isolates, and the ones which caused the greater percentage of insect mortality were used in concentration tests (0, 5, 10, 20, 50 Infective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
12
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 16 publications
2
12
1
1
Order By: Relevance
“…Virulence variability for isolates from different species of nematodes on the same host was expected (Lewis et al, 2006), and has already been reported in the work of Ferreira et al (2015) for D. brevipes and other similar species of mealybugs Alves et al, 2009a;Andaló et al, 2004a;Guide et al, 2016). The factors that may contribute to the difference in interspecific virulence include morphological differences, behavioral habits (foraging strategy), co-evolution with the host insect, as well as the various factors that involve the symbiotic nematode-bacteria complex during the infection process (Alonso et al, 2018;Shapiro-Ilan et al, 2017;Simoes and Rosa, 1996).…”
Section: Isolate Selection Testsupporting
confidence: 61%
See 1 more Smart Citation
“…Virulence variability for isolates from different species of nematodes on the same host was expected (Lewis et al, 2006), and has already been reported in the work of Ferreira et al (2015) for D. brevipes and other similar species of mealybugs Alves et al, 2009a;Andaló et al, 2004a;Guide et al, 2016). The factors that may contribute to the difference in interspecific virulence include morphological differences, behavioral habits (foraging strategy), co-evolution with the host insect, as well as the various factors that involve the symbiotic nematode-bacteria complex during the infection process (Alonso et al, 2018;Shapiro-Ilan et al, 2017;Simoes and Rosa, 1996).…”
Section: Isolate Selection Testsupporting
confidence: 61%
“…Even in other cultures, the management of these insects is considered unsatisfactory, due to their underground their habits, which impedes control by most natural enemies and agricultural pesticides Heterorhabditis amazonensis and H. indica on D. brevipes: Zart et al (Alves and Moino, 2009;Guide et al, 2016;Souza and Ribeiro, 2003).…”
mentioning
confidence: 99%
“…Other studies, under laboratory and greenhouse conditions, demonstrated the virulence of isolates of genera Steinernema and Heterorhabditis in the coffee root mealybug Dysmicoccus spp. (Hemiptera: Pseudococcidae) (ANDALÓ et al, 2004;ALVES et al, 2009a;GUIDE et al, 2016). These differences can be explained by the specificity of different isolates for different hosts due to several factors, such as its efficiency reaching the host, penetrating and causing infection, and the ability to "trick" the insect's immune system (LEWIS et al, 2006).…”
Section: Selection Of Isolatesmentioning
confidence: 99%
“…The persistence of entomopathogens in the environment is an important characteristic of biological control programs, and some studies have proven the high persistence of several species of EPNs under field conditions (DEL VALLE et al, 2008;ALVES et al, 2009b;GUIDE et al, 2016).…”
Section: Greenhouse Test and Evaluation Of The Persistence Of Steinermentioning
confidence: 99%
“…La présence de poils (pubescence) sur la plante repoussant ou gênant les ravageurs lors de leurs déplacements ou pendant la ponte en est une illustration ; -chimique ou biologique (antibiose), la plante émet des substances chimiques qui repoussent ou intoxiquent le ravageur. (Guide et al, 2016).…”
Section: Sélection Variétaleunclassified